Let the sum of n, 2n, 3n terms of an A.P. be S1, S2 and S3, respectively,


Let the sum of $n, 2 n, 3 n$ terms of an A.P. be $S_{1}, S_{2}$ and $S_{3}$, respectively, show that $S_{3}=3\left(S_{2}-S_{1}\right)$


Let a and b be the first term and the common difference of the A.P. respectively.


$\mathrm{S}_{1}=\frac{n}{2}[2 a+(n-1) d]$ $\ldots(1)$

$\mathrm{S}_{2}=\frac{2 n}{2}[2 a+(2 n-1) d]=n[2 a+(2 n-1) d]$ $\ldots(2)$

$\mathrm{S}_{3}=\frac{3 n}{2}[2 a+(3 n-1) d]$ $\ldots(3)$

From (1) and (2), we obtain

$\mathrm{S}_{2}-\mathrm{S}_{1}=n[2 a+(2 n-1) d]-\frac{n}{2}[2 a+(n-1) d]$

$=n\left\{\frac{4 a+4 n d-2 d-2 a-n d+d}{2}\right\}$

$=n\left[\frac{2 a+3 n d-d}{2}\right]$

$=\frac{n}{2}[2 a+(3 n-1) d]$

$\therefore 3\left(\mathrm{~S}_{2}-\mathrm{S}_{1}\right)=\frac{3 n}{2}[2 a+(3 n-1) d]=\mathrm{S}_{3}$ [From (3)]

Hence, the given result is proved.


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now